Pelatihan Pembuatan Sasirangan Media Baju Kaos Peluang Usaha Anak Panti Asuhan Yatim Putra Muhammadiyah Banjarmasin - Yusri Yusri; Faisal Rahman; Muhammad Mahendra Abdi (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
Lack of knowledge and skills in developing sasirangan t-shirt media which can be used as profitable business opportunities, there is no initiator of the sasirangan t-shirt business among young people at the Banjarmasin Muhammadiyah Orphanage. Community Service Providing training and education related to sasirangan cloth, innovation in the form of t-shirts, providing motivation and inspiration for creative entrepreneurship as business opportunities that can be developed with the hope that there will be interest in developing into independent creative businesses. The method used is lectures providing material and direct practice. As a result of this training, the young people at the Yatim Putra Muhammadiyah Orphanage were able to understand and practice it directly in the process of making sasirangan using t-shirt media with the given working mechanism. Of the fifteen participants who took part in this training, all of them succeeded in making sasirangan t-shirts which were shown in the final process where the participants had gone through a series of manufacturing stages starting from drawing patterns, basting, threading, dyeing colors, releasing threads to drying. From this training, it can be concluded that all participants, the majority of whom are male, have talent in making this sasirangan and have an interest in being able to create according to trendy and contemporary motifs as a business opportunity independently or in groups for young people as a source of income for the children of the orphanage in supporting economy.